Abducens nerve palsy in a congenital anomalous neurovascular development of the sixth cranial nerve and anterior inferior cerebellar artery: A case report - Silvia Canovetti, MD; Livia Pasquali, MD; Gianfranco Di Salle, MD; Giacomo Lucchi, MD; Graziella Donatelli, MD; Mirco Cosottini, MD (Radiology Case Reports, 2022)
Abducens nerve palsy is a common ocular motor paralysis with a broad set of etiopathogenetic causes. Magnetic resonance imaging is a key diagnostic technique to investigate organic causes of sixth nerve palsy, as it allows a detailed representation of the course of the nerve, particularly in its intracisternal tract. Anatomical variants of the sixth cranial nerve comprise duplications and fenestrations in various traits. Anatomical variants of cerebellar arteries have also been described. We report the case of a patient with abducens nerve palsy presumably related to a neurovascular conflict due to a peculiar anatomical variant, which consists in a cerebellar artery passing through the intracisternal duplication of the abducens nerve.